2023
DOI: 10.1039/d3ra05875a
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the activity of Ca2Fe2O5 additives on the thermochemical energy storage performance of limestone waste

Rehan Anwar,
Rajani K. Vijayaraghavan,
Patrick J. McNally
et al.

Abstract: Activation energy for CaCO3 calcination reaction was reduced using Ca2Fe2O5 additives which improved the thermochemical cycling capacity of limestone waste.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Anwar et al reported that a Ca 2 Fe 2 O 5 additive lowered the decomposition activation energy of limestone waste from 182.3 to 162.3 kJ mol −1 . 36 CaCO 3 –Al 2 O 3 (20 wt%) was also reported with an activation energy of 169 ± 17 kJ mol −1 . 11 Here, the estimated activation energy is closer to the value of 206 kJ mol −1 calculated by Olszak-Humienik et al for the decomposition of natural dolomites and the 234 kJ mol −1 by Ptáček et al for thermal decomposition of ferroan dolomites in inert atmosphere.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Anwar et al reported that a Ca 2 Fe 2 O 5 additive lowered the decomposition activation energy of limestone waste from 182.3 to 162.3 kJ mol −1 . 36 CaCO 3 –Al 2 O 3 (20 wt%) was also reported with an activation energy of 169 ± 17 kJ mol −1 . 11 Here, the estimated activation energy is closer to the value of 206 kJ mol −1 calculated by Olszak-Humienik et al for the decomposition of natural dolomites and the 234 kJ mol −1 by Ptáček et al for thermal decomposition of ferroan dolomites in inert atmosphere.…”
Section: Resultsmentioning
confidence: 77%
“…Anwar et al measured a similar conversion for their sample with a Ca : Fe ratio of 1 : 1 after 40 cycles. 36 Information on the reaction kinetics are available in Fig. S1 (ESI†).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limestone is decomposed into CaO and CO 2 by absorbing heat (calcination), while during the reverse reaction the heat is released (carbonation). This approach offers numerous advantages, including low material cost (approximately $10 per tonne for CaCO 3 /CaO), widespread availability, nontoxicity, exceptionally high energy density (reaching up to 4 GJ m −3 ) and reaction enthalpy (∆H 860 • C = 165.9 kJ) [95], operation at very high temperatures (exceeding 800 • C), catalyst-free operation, byproductfree reactions, and extensive experimental validation from Carbon Capture and Storage (CCS) applications [58].…”
Section: Limestone-based Thermochemical Energy Storagementioning
confidence: 99%